48. Dosimetric predictors of radiation induced alopecia in brain tumours proton therapy. (December 2018) - Taffelli, A.; Amelio, D.; Fellin, F.; D'Avino, V.; Palma, G.; Tommasino, F.; Scifoni, E.; Durante, M.; Schwarz, M.; Amichetti, M.; Cella, L.
Abstract : Purpose: Hair follicles are very sensitive to radiation, and radiation may induce temporary or permanent alopecia. Our aim was to determine dose predictors for radiation-induced alopecia (RIA) in patients treated with proton therapy (PT) for brain tumours (BT). Methods: We evaluated 72 consecutive BT patients undergoing PT by pencil beam scanning at Trento Proton Therapy Center (median dose, 50.4 Gy; range, 36–72 Gy) in a study prospectively assessing acute and late RIA classified according to the CTCAE v.4 scoring system. Median patient age was 56 years (range, 30–84). Median follow-up was 5 months (range, 1–19). Results: Acute Grade 2 RIA was found in 34 of 69 (49%) patients at a median time of 1.2 months (range, 0–2.3) from the end of PT; late Grade 2 RIA was found in 18 of 59 patients (31%) at a median time of 4.1 months (range, 3–19). Acute G2 RIA events were significantly correlated with late events (p < 0.0001). Younger age at irradiation was the only clinical risk factor for acute G2 RIA ( p < 0.006). The relative scalp surface receiving at least 20 Gy (RS20) was significantly associated to late G2 RIA (p = 0.033). Median RS20 was 11% (range, 0–40%) in patients developing G2 RIA and 2.9% (range, 0–59%) in who did not (Figure). A trend for RS40 and acute G2 RIA correlation was found (p = 0.07). Conclusions: We found a significant correlation between the occurrence of late G2 RIA and scalp RS20 in BT patients receiving PT. Further studies are needed to determine if the observed RIA is only temporary or permanent.